Kilka uwag o konstytucyjnej regulacji instytucji głowy państwa w Republice Łotewskiej(ze szczególnym uwzględnieniem antecedencji historycznych i specyfiki rozwiązań ustrojowych) - Kierończyk, Przemysław (PRAWO i WIĘŹ, 2026)
This paper aims to introduce the Polish reader to some of the specifics of Latvian constitutional solutions. The author primarily discusses the particulars of the Latvian constitution, a unique example of a legal act that had been practically ineffective for many years being restored to its former binding force. In the 1990s, Latvia restored the legal force of the 1922 constitution, which had ceased to be in force in 1934 following the coup d’état (i.e. before the Soviet occupation of the country). In this context, the paper draws attention to the values that guided the creators of this constitution and the historical events that formed its foundation. The author attempts to identify solutions that are specific to Latvia and that define the relationship between the executive power (primarily the president) and the legislature. Ultimately, the author concludes that it is justified to view the Latvian constitutional solutions as a specific form of rationalisation of the parliamentary-cabinet system. The main argument in favour of this view is the unique solution of the president actually being politically responsible before parliament. The final section of the paper considers the potential for adopting certain Latvian solutions in the event of changes to the Polish constitution.